Manufacturing technology for aerospace structural materials - Campbell, F. C. (Flake C.); ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2006)
Safe flight depends on this information.
Cover; Contents; Preface; Introduction; Aluminum; Magnesium and Beryllium; Titanium; High Strength Steels; Superalloys; Polymer Matrix Composites; Adhesive Bonding and Integrally Cocured Structure; Metal Matrix Composites; Ceramic Matrix Composites; Structural Assembly; Metric Conversions; A Brief Review of Materials Fundamentals; Mechanical and Environmental Properties; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Aerospace engineering -- Materials; Manufacturing processes; TRANSPORTATION -- Aviation -- General; Manufacturing processes; Electronic books